RETRACTED: Synergistic combination of violacein and azoles that leads to enhanced killing of major human pathogenic dermatophytic fungi Trichophyton rubrum - Anju, S.; Kumar, Nishanth S.; Krishnakumar, B.; Kumar, B. S. Dileep (Frontiers in Cellular and Infection Microbiology, 2015)
Superficial mycoses caused by dermatophytic fungi such as Trichophyton rubrum represent the most common type of worldwide human infection affecting various keratinized tissues in our body such as the skin, hair and nails, etc. The dermatophytic infection is a significant public health threat due to its persistent nature and high recurrence rates, and thus alternative treatments to cure this fungal infection are urgently required. The present study mainly focused on the synergistic activity of violacein with four azole drugs (ketoconazole, fluconazole, clotrimazole, and itraconazole) against T. rubrum. The synergistic antifungal activities of violacein and azoles were measured by checkerboard microdilution and time-kill assays. In our study, combinations of violacein and azoles predominantly recorded synergistic effect (FIC index < 0.5). Significant synergistic value was recorded by the combination of violacein and clotrimazole. Time-kill assay by the combination of MIC concentration of violacein and azoles recorded that the growth of the T. rubrum was significantly arrested after 4-12 h of treatment. The combination of violacein and azoles leads to the enhanced inhibition of mycelial growth and conidial germination. Moreover combination enhanced the rate of release of intracellular materials. Morphological changes by SEM analysis were also prominent with the combination. A normal human cell line [Foreskin (FS) normal fibroblast] was used to check the cytotoxicity of violacein. Interestingly violacein recorded no cytotoxicity up to 100 µg/ml. The in vitro synergistic effect of violacein and azoles against clinically relevant fungi, T. rubrum, is reported here for the first time. Finally, our findings support the potential use of the violacein as an antifungal agent especially against dermatophytic fungi T. rubrum.